Chromatographic behaviour in reversed-phase high-performance liquid chromatography with micellar and submicellar mobile phases: effects of the organic modifier - Fischer, J; Jandera, P (Journal of chromatography. B, Biomedical applications, 1996)
Continuing our earlier study of the retention behaviour in reversed-phase systems with aqueous mobile phases containing surfactants in concentrations lower (submicellar systems) and higher (micellar systems) than the critical micellar concentration (CMC), we investigated the chromatographic behaviour of various non-ionic solutes in mixed aqueous-organic micellar and submicellar mobile phases and their dependence on the methanol concentration. CMC values were measured for two cationic surfactant and one anionic surfactant in mixed aqueous-methanolic solvents, and were found to increase slightly with increasing methanol concentration. Depending on the character of the surfactant, a limiting concentration of methanol was found, above which micelles do not occur anymore. Sorption isotherms of the surfactants on an octylsilica gel column were measured as a function of the concentration of methanol in aqueous-methanolic solvents. A modified Langmuir equation was used to describe the distribution of the surfactants between the stationary and the mobile phases in the concentration range below CMC. The retention of several polar solutes was measured on an octylsilica gel column both in micellar and submicellar mobile phases containing methanol. The dependencies of the capacity factors of the solutes studied on the concentration of methanol in the mobile phase can be suitably described by the same form of equation as that conventionally used for aqueous-organic mobile phases that do not contain surfactants, but the slopes of the dependencies for a given solute are different in the two ranges of surfactant concentrations. The ratio of the two slopes is controlled by the interaction with micelles and is approximately equal to, below or above 1, depending on whether the solutes do or do not associate with the micelles, or are repulsed from them. Simultaneous control of the concentrations of the organic solvent and of the surfactant in the mobile phase can be used for fine tuning the selectivity of separation as a complement to commonly used adjusting concentrations of two organic solvents in ternary aqueous-organic mobile phases. These effects are illustrated by practical examples of submicellar HPLC with mobile phases containing methanol.
Keywords: Solvents; kvartérní amoniové sloučeniny; vysokoúčinná kapalinová chromatografie; osmolární koncentrace; Methanol; Detergents; Water; Cetrimonium Compounds; Adsorption; methanol; rozpouštědla; povrchově aktivní látky; detergenty; cetrimoniové sloučeniny; dodecylsíran sodný; adsorpce; Sodium Dodecyl Sulfate; Cetrimonium; micely; voda; Quaternary Ammonium Compounds; Chromatography, High Pressure Liquid; Surface-Active Agents; Micelles; cetrimonium; Osmolar Concentration